The Effect of Animosity and Religiosity on Boycott Behavior of Halal-Certified Foreign Restaurants - Alam, Azhar; Salsabila, Kultsum Hanifah; Singh, Keshminder Singh Jit; Nordin, Nadhirah (International Journal of Accounting and Economics Studies, 2025)
This study aimed to examine the effects of animosity and religiosity on boycott behavior toward halal-certified foreign restaurants in the context of the Israeli-Palestinian conflict, while assessing religiosity’s moderating role. Using a quantitative approach with Structural Equation Modeling based on Partial Least Squares, data were collected from 213 Indonesian respondents who had visited such restaurants. The analysis revealed that animosity and religiosity positively and significantly affect boycott behavior. However, religiosity did not significantly moderate the relationship between animosity and boycott behavior, nor between boycott intention and boycott behavior. These findings indicate that animosity and religiosity independently drive boycott actions, whereas the anticipated moderating role of religiosity was not supported. The study’s contribution lies in its nuanced identification of socio-political and religious factors shaping consumer boycotts in conflict. The generalizability of results is limited by the young and predominantly female sample and the focus on a specific geographical context. The insights provided may inform marketing strategies and policy interventions related to consumer responses in similar settings.